Using common worship: times and seasons: lent to embertide: a practical guide - Kennedy, David; Haselock, Jeremy; Greenacre, Roger (London, UK: Church Publishing House, 2008)
Offers guidance from the Liturgical Commission on best practice in using Times and Seasons from Lent to Embertide. It uses practical tips and illuminating case studies to encourage creative use of the Common Worship liturgy in your church.
Includes index.
Keywords: Lent -- Liturgy -- Church of England; Embertide -- Liturgy -- Church of England